The Impact of Information Overload on Art Appreciation Patterns in the Digital Era - Putri Gracia Simatupang; I Gede Yudarta; Ni Wayan Ardini (Institut Seni Indonesia Bali, 2026)
The phenomenon of information overload arising from the flood of data in the digital era has impacted almost all aspects of life, including patterns of art appreciation. This article aims to examine how information overload, particularly through social media and digital spaces, is changing the way society understands, evaluates, and enjoys works of art. This study uses a qualitative approach with literaturea analysis and a critical examination of contemporary visual culture phenomena. The results show that art appreciation, which was previously reflective and in-depth, has shifted toward a consumerist, instantaneous, and digital popularity-based pattern. The appreciation process is now more often determined by algorithmic logic, virality, and the speed of information distribution, rather than the aesthetic value and intrinsic meaning of the artwork itself. This change poses a challenge for artists and art institutions to maintain the quality of art appreciation amidst the rapid flow of digital information.